Dynamic Redundancy Forward Error Correction Mechanism for the Enhancement of Internet-Based Video Streaming - Al-Momani, Omar Mohammad Deeb (2010)
Video streaming applications over the Internet is suffering many challenges and packet loss is one of the main challenges. This is a result of best-effort services provided by existing IP networks, which does not guarantee packet delivery. Therefore, Forward Error Correction(FEC) is a mechanism used to alleviate the effect of packet losses in the Internet by adding fixed extra packets known as parity packets or redundant packets, which are used to reconstruct the original packets in the event of losses. The use of redundant packet resulted in more consumed bandwidth and increased end-to-end delay. This thesis is concerned with the design and evaluation of FEC error control mechanism. We aimed at addressing the problems faced by the existing FEC mechanism. Thus, a performance evaluation methodology via network simulation and a defined set of key evaluation criteria to test the existing FEC mechanisms under different network conditions and scenarios can be established. Having learnt from evaluation and analyses of existing FEC mechanisms, we found that using a fixed number of redundant packets worsens network performance and video quality. Therefore, an innovative FEC mechanism, called Dynamic Redundancy FEC (DRFEC) is proposed. The design goals of the mechanism are to enhance the video streaming quality over existing IP network by reconstructing loss packets and to enhance network performance by minimising delay and consumed bandwidth. The proposed mechanism was implemented in simulation environment using the NS2 network simulation package. After implementation and verification of these codes in NS2, the performance evaluation of the proposed mechanism was performed. The performance analysis and simulation experiments showed that our proposed mechanism of DRFEC performs better in comparison with the other FEC mechanisms. The DRFEC mechanism was tested with the most used queue polices in today's Internet router, which are the Drop Tail and Random Early Detection queue policies, and with different queue sizes. The results showed that, using the DRFEC mechanism can decrease the consumed bandwidth as compared with the other FEC mechanisms and using the DRFEC mechanism can also decrease the delay as compared with the other FEC mechanisms. Therefore, based on the findings of this study, using DRFEC is a potentially viable mechanism of improving the network performance and video quality.